Ten-year surveillance and epidemiological patterns of measles and rubella: A study in the Babol County - Amir-hossein Alizadeh; Hossein-Ali Nikbakht; Mohammad–Ali Jahani; Seyedeh-Niko Hashemi; Sharareh Asadi (Caspian Journal of Internal Medicine)
Background: The trend of measles and rubella has changed over the last two decades, with the increase in vaccination coverage and the establishment of the surveillance system. This study aimed to demonstrate the current status of the surveillance system and the epidemiological trend of measles and rubella. Methods: This cross-sectional study retrospectively investigated the status of the surveillance system and the epidemiological patterns of measles and rubella in Babol Mazandaran, during 2014-2023. The study included 348 patients diagnosed with rubella and measles (suspected and definite). Their information was obtained and analyzed from the health department's information registration system. Results: Out of 348 suspected cases (272 suspected cases of rubella and 76 suspected cases of measles), 2 cases were identified as rubella and 1 case as confirmed measles. 108 (31.03%) cases of suspected cases were in the age group below one year and 153(43.97%) cases were in the age group of 1 to 6 years. The age-specific incidence has decreased with increasing age (p <0.001), and the incidence of suspected cases has increased from 2014 to 2023 (p <0.001). The proportion of appropriate laboratory sample collection before and after COVID-19 was 100%. However, the source of infection remained unknown for all confirmed cases. Conclusion: The quality of data, timeliness, and sensitivity of the health surveillance system in the region under study are acceptable. However, continuous training for healthcare providers and upgrading the equipment and facilities at the regional level are needed to maintain and improve this situation.